Carbohydrate ingestion improves performance of a new reliable test of soccer performance - Currell, K.; Conway, S.; Jeukendrup, A. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
The aim of the study was to investigate the reliability of a new test of soccer performance and evaluate the effect of carbohydrate (CHO) on soccer performance. Eleven university footballers were recruited and underwent 3 trials in a randomized order. Two of the trials involved ingesting a placebo beverage, and the other, a 7.5% maltodextrin solution. The protocol comprised a series of ten 6-min exercise blocks on an outdoor Astroturf pitch, separated by the performance of 2 of the 4 soccer-specific tests, making the protocol 90 min in duration. The intensity of the exercise was designed to be similar to the typical activity pattern during soccer match play. Participants performed skill tests of dribbling, agility, heading, and shooting throughout the protocol. The coefficients of variation for dribbling, agility, heading, and shooting were 2.2%, 1.2%, 7.0%, and 2.8%, respectively. The mean combined placebo scores were 42.4 ± 2.7 s, 43.1 ± 3.7 s, 210 ± 34 cm, and 212 ± 17 points for agility, dribbling, heading, and kicking, respectively. CHO ingestion led to a combined agility time of 41.5 ± 0.8 s, for dribbling 41.7 ± 3.5 s, 213 ± 11 cm for heading, and 220 ± 5 points for kicking accuracy. There was a significant improvement in performance for dribbling, agility, and shooting (p < .05) when CHO was ingested compared with placebo. In conclusion, the protocol is a reliable test of soccer performance, and ingesting CHO leads to an improvement in soccer performance.